2023
DOI: 10.26434/chemrxiv-2023-lrt19
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High-Concentration Self-Assembly of Zirconium- and Hafnium-Based Metal-Organic Materials

Abstract: Metal–organic frameworks (MOFs) are crystalline, porous solids constructed from organic linkers and inorganic nodes that are promising for applications in chemical separations, gas storage, and catalysis, among many others. However, a major roadblock to the widespread implementation of MOFs, including highly tunable and hydrolytically stable Zr- and Hf-based frameworks, is their benchtop-scalable synthesis, as MOFs are typically prepared under highly dilute (≤0.01 M) solvothermal conditions. This necessitates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…In particular, the need for liters of solvent(s) and disproportionate quantities of acid modulators often limit MOF synthesis to sub-gram quantities. Recently, Matzger and coworkers, 137 along with our group, 138 have found that much higher reaction concentrations (up 1 M in some cases) can be used to produce high-quality MOFs with significantly reduced solvent waste. In a similar vein, we carried out a structure-property study to identify the optimal modulator for Zr-MOF synthesis, with the goal of reducing the amount of modulator required to produce highly crystalline material.…”
Section: Robustness Of Mofs For Organic Synthesismentioning
confidence: 99%
“…In particular, the need for liters of solvent(s) and disproportionate quantities of acid modulators often limit MOF synthesis to sub-gram quantities. Recently, Matzger and coworkers, 137 along with our group, 138 have found that much higher reaction concentrations (up 1 M in some cases) can be used to produce high-quality MOFs with significantly reduced solvent waste. In a similar vein, we carried out a structure-property study to identify the optimal modulator for Zr-MOF synthesis, with the goal of reducing the amount of modulator required to produce highly crystalline material.…”
Section: Robustness Of Mofs For Organic Synthesismentioning
confidence: 99%
“…We anticipate that these findings will guide the development of high-concentration syntheses of other MOFs. Two desirable outcomes can be envisaged: the formation of the same phase as the reaction concentration is increased, which allows for MOFs to be prepared with significantly reduced solvent use, [12][13][14] or the formation of new phases with distinct properties from known combinations of linkers and metal salts. As such, high-concentration solvothermal synthesis should be added to the growing lexicon of methods available for the synthesis of MOFs and other metal-organic materials.…”
Section: Photophysical Analysis Of H4dobdc Corn-mof-1 (Mg) and Mg2(do...mentioning
confidence: 99%
“…8 Unfortunately, the large solvent volumes required for traditional solvothermal synthesis necessitate the use of liters of solvent to produce sub-gram quantities of MOF, contributing greatly to the cost of MOFs on scale and generating significant waste. 11 Solvothermal MOF syntheses at higher concentrations are rare, [12][13][14][15][16] as poorly crystalline or low surface area materials are typically isolated instead due to the rapid precipitation of products from solution. 13,[17][18][19][20][21] The MOF-74, CPO-27, or M2(dobdc) (M = Mg, Mn, Fe, Co, Ni, Cu, Zn, Cd; dobdc 4− = 2,5-dioxido-1,4-benzenedicarboxylate) family of frameworks embodies the aforementioned synthetic challenges (Figure 1).…”
Section: Introductionmentioning
confidence: 99%